Cloud Migration in Enterprise HR Systems: A Longitudinal Study of SAP HCM's Evolution and Organizational Impact - Vijayaratnam Sirangula, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The transition from on-premise human capital management systems to cloud-based solutions represents a significant shift in enterprise resource planning, particularly within SAP's ecosystem. This article examines the evolution of SAP HCM, analyzing its transformation from traditional on-premise deployments to cloud-based SuccessFactors solutions. Through a comprehensive article review of technological innovations, implementation strategies, and organizational impacts, this article explores the multifaceted implications of this digital transformation on HR processes, data management, and user experience. The article investigates critical aspects including migration methodologies, security considerations, and the enhancement of core HR functions such as recruitment, payroll, and talent management. By analyzing the architectural changes, integration challenges, and operational benefits, this study provides insights into the broader implications of cloud adoption in enterprise HR systems. The findings contribute to both theoretical understanding and practical knowledge of enterprise system evolution, while offering valuable perspectives for organizations contemplating similar transformational initiatives in their HR technology landscape.
Keywords: SAP HCM Cloud Migration; Enterprise HR Transformation; SuccessFactors Implementation; Digital HR Architecture; Cloud-based Human Capital Management